Science Monitoring And Reliable Technology (SMART) to monitor the ocean using submarine cables - Sifón, Matías (The International Hydrographic Review, 2025)
The Ocean is a fundamental part of life on Earth and therefore its observation is essential; however, there are currently no seabed monitoring networks that cover large areas. The Science Monitoring and Reliable Telecommunications (SMART) Cables initiative aims to combine the growing telecommunications industry with ocean sciences, leveraging the infrastructure of the former to deploy sensors to obtain essential ocean data on the seafloor in real time.